Case Report: Recombinant Human Endostatin Plus Chemotherapy for Epidermal Growth Factor Receptor-Negative Miliary Lung Adenocarcinoma - Zhu, Jian; Xu, Ya; Huang, Wen-Cai; Ji, Tao; Ai, Guo-Ping; Gao, Yan-Hong (Frontiers in Oncology, 2022)
Except for the traditional chemotherapy, few treatments strategy about miliary intrapulmonary carcinomatosis (MIPC) have been reported in the existing literature. In this report, we primarily discussed the possible etiology and the potentially effective treatment options for a patient with MIPC who benefited from combined treatment. A nonsmoking woman was diagnosed with MIPC at an advanced stage. Gene detection showed an EGFR negative status. She accepted first-line chemotherapy with pemetrexed and cisplatin, and the tumor progressed. Next, PD-1 inhibitors plus pemetrexed and cisplatin were administered, and the tumor remained uncontrolled. After two cycles of recombinant human endostatin plus second-line chemotherapy, the numerous pulmonary nodules had all nearly completely disappeared, while an accentuated decrease in the primary tumor volume was observed. Moreover, biochemical markers, including the patient's tumor markers, also trended toward normal. This report describes the first case of a MIPC patient who significantly responded to antiangiogenic therapy combined with chemotherapy. Anti-angiogenic therapy may be a possible strategy for the EGFR-negative lung adenocarcinoma population.